General practices as emergent research organizations: a qualitative study into organizational development. - Macfarlane, F; Shaw, S; Greenhalgh, T; Carter, Y (2005)
BACKGROUND: An increasing proportion of research in primary care is locally undertaken in designated research practices. Capacity building to support high quality research at these grass roots is urgently needed and is a government priority. There is little previously published research on the process by which GP practices develop as research organizations or on their specific support needs at organizational level. METHODS: Using in-depth qualitative interviews with 28 key informants in 11 research practices across the UK, we explored their historical accounts of the development of research activity. We analysed the data with reference to contemporary theories of organizational development. RESULTS: Participants identified a number of key events and processes, which allowed us to produce a five-phase model of practice development in relation to research activity (creative energy, concrete planning, transformation/differentiation, consolidation and collaboration). Movement between these phases was not linear or continuous, but showed emergent and adaptive properties in which specific triggers and set-backs were often critical. CONCLUSION: This developmental model challenges previous categorical taxonomies of research practices. It forms a theory-driven framework for providing appropriate support at the grass roots of primary care research, based on the practice's phase of development and the nature of external triggers and potential setbacks. Our findings have important implications for the strategic development of practice-based research in the UK, and could serve as a model for the wider international community.